Le rôle du droit international - Suy, Érik (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
All countries are equally sovereign and the faculty to contract international obligations is precisely an attribute of that sovereignty. Does this imply that when Human Rights are the object of international accords the signing countries abandon a part of their sovereignty ? It depends, of course, on the nature of the obligations that have been contracted. The author analyses the principal international instruments relating to Human Rights and evaluates the impact of obligations which affect the sovereignty of adhering countries.